Epidemiological Features of New Coronavirus Infection (COVID-19). Communication 1: Modes of Implementation of Preventive and Anti-Epidemic Measures - V. V. Kutyrev; A. Yu. Popova; V. Yu. Smolensky; E. B. Ezhlova; Yu. V. Demina; V. A. Safronov; I. G. Karnaukhov; A V. Ivanova; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2020)
The review analyses the information on the epidemiological situation on COVID-19 around the world. Presented is the assessment of the major epidemiological parameters (basic reproductive rate, lethality, incubation period, and serial interval). Demonstrated is the share of severe cases among different age groups and the general structure of incidence by the severity of clinical course. The paper provides the classification of response models internationally depending upon the complex of measures undertaken at different stages of epidemic process. Reviewed are the key response actions to control the COVID-19 transmission in different countries of the world and the Russian Federation and given is the assessment of their effectiveness.